Local dose rate effects in implantable cardioverter-defibrillators with flattening filter free and flattened photon radiation - Gauter-Fleckenstein, Benjamin; Tueluemen, Erol; Rudic, Boris; Borggrefe, Martin; Polednik, Martin; Fleckenstein, Jens (Strahlentherapie und Onkologie, 2022)
In the beam penumbra of stereotactic body radiotherapy volumes, dose rate effects in implantable cardioverter-defibrillators (ICDs) may be the predominant cause for failures in the absence of neutron-generating photon energies. We investigate such dose rate effects in ICDs and provide evidence for safe use of lung tumor stereotactic radioablation with flattening filter free (FFF) and flattened 6 Megavolt (MV) beams in ICD-bearing patients.